An Environment-Oriented PBL Digital Worksheet to Support Critical Thinking Development in Ecosystem Learning - Syifa Salsabila; Widia Astuti; Ernawati Ernawati; Maretik Maretik; Miswandi Tendrita (Universitas Labuhanbatu, 2025)
Background: The development of students’ critical thinking skills requires learning media that actively engage students in problem analysis, reasoning, and decision-making processes. However, the use of electronic student worksheets (E-LKPD) in schools is still limited and often does not fully integrate problem-based learning principles or contextual environmental issues. Many available LKPDs remain procedural and teacher-centered, reducing opportunities for students to practice higher-order thinking skills independently. This condition indicates the need for innovative E-LKPD that are systematically designed to support critical thinking development through problem-based learning approaches. This study aims to develop and evaluate the effectiveness of an environment-based Problem-Based Learning (PBL) electronic student worksheet (E-LKPD) on ecosystem content to enhance senior high school students’ critical thinking skills. Methodology: This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The product was validated by two experts using a Likert-scale-based expert validation questionnaire covering content, media, and language aspects. Practicality testing involved one biology teacher and nineteen students, while effectiveness was analyzed using a pretest–posttest design with the Shapiro–Wilk test and paired t-test. Findings: The validation results obtained an average percentage of 91%, categorized as very valid. Practicality testing involving 1 teacher and 19 students SMAN 1 Toari showed positive responses with a percentage of 84%, classified as very practical. The effectiveness of the E-LKPD was evidenced by an increase in the average score from 82.68 to 89.46 among students of class X.4 at MAN 1 Kolaka, along with a significance value of 0.000, indicating a significant difference after the implementation of the E-LKPD. Contribution: These findings indicate that the environmental-based PBL E-LKPD contributes to the design of biology learning by providing a structured and interactive digital worksheet that facilitates problem-oriented learning and critical thinking development. The integration of contextual environmental issues within the E-LKPD supports meaningful ecosystem learning and reinforces the role of digital learning media in promoting active, analytical, and student-centered biology instruction